2022
DOI: 10.2147/ptt.s349791
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Exercise: A Review

Abstract: Psoriasis is a prevalent inflammatory skin disorder that is associated with a number of comorbidities including cardiovascular disease and metabolic syndrome. Exercise can influence the outcomes of chronic inflammatory diseases, and the presence of these diseases can also influence physical activity in afflicted patients. We reviewed the available literature published on exercise in psoriasis patients and aimed to explore physical activity levels, barriers to exercise, physical fitness, exercise as a preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Physical inactivity, defined as “An insufficient physical activity level to meet present physical activity recommendations” [ 74 ], is one of the crucial factors responsible for obesity and abdominal fatness [ 75 ]. Fat cells (adipocytes) are a source of pro-inflammatory adipokines (leptin and resistin).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Physical inactivity, defined as “An insufficient physical activity level to meet present physical activity recommendations” [ 74 ], is one of the crucial factors responsible for obesity and abdominal fatness [ 75 ]. Fat cells (adipocytes) are a source of pro-inflammatory adipokines (leptin and resistin).…”
Section: Resultsmentioning
confidence: 99%
“…They can induce T helper 17 cells secreting pro-inflammatory cytokines (TNF-α and IL-6) and CRP [ 76 ]. Obesity, fatness, and physical inactivity are likely critical risk factors for psoriasis development [ 75 ]. Evidence has shown that regular physical exercise (PE) of moderate intensity (50–<60% VO 2 max) (e.g., walking, dancing, yoga, badminton, downhill skiing, gardening) is an important factor regulating ROS/RNS levels in cells, protecting them against low levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the pathological manifestations of PsO (phenotype) are the product of the intricate interaction between genetic susceptibility [ 15 ] and environmental factors (i.e., diet or circadian rhythm) [ 16 ] ( Figure 1 ). Several studies pointed out that in western societies, unhealthy lifestyles may deeply condition the PsO march and flare frequency; in particular, unbalanced diets (i.e., western diet) with high fat and/or high sugar [ 17 , 18 ], inadequate sleep [ 19 ] and insufficient physical activity [ 20 ] may be triggers. Furthermore, all these PsO triggers may converge in creating gut dysbiosis [ 21 ], not necessarily identifiable as small intestinal bacterial overgrowth (SIBO) [ 22 ], but potentially critical for PsO and psoriatic arthritis (PsA) flares.…”
Section: Introductionmentioning
confidence: 99%